Peranan Tari Janger Klasik Dalam Penanaman Sikap Cinta Seni Budaya di Organisasi Kepemudaan Banjar Pesalakan, Desa Pejeng Kangin, Gianyar - Ni Wayan Iriani; Kusuma, Putu Sandra Devindriati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the role of the Classical Janger Dance activity in fostering an attitude of love for arts and culture in the youth organization Sekaa Teruna Teruni (STT) Tri Dharma Bakti Banjar Pesalakan, Pejeng Kangin Village, Tampak Siring, Gianyar, Bali. This study uses a qualitative research method and was held in Banjar Pesalakan. Data were obtained through direct observation and documentation regarding the profile of STT Tri Dharma Bakti and interviews with the Kelian of Banjar Pesalakan and the Classical Janger Dance instructor. The results indicate that the role of the Classical Janger Dance activity is as a form to introduce arts and Balinese songs, which contains moral learning values, good character and national character education. Concerns about the absence of the younger generation preserving Balinese arts and culture due to economic needs, becoming tourism actors, studying far from the village are the reasons that drive the desire of kelian banjar to form a Classical Janger Dance group for young people at STT. Indirectly, learning the Classical Janger Dance has a very important role in shaping the character of the younger generation, a tolerance, a mutual respect for one another, patience, fostering self-confidence, a spirit of mutual cooperation and fostering a love for the attitude of the younger generation, continuing and preserving the Classical Janger Dance. Thus, the younger generation of STT can play a role and preserve Balinese traditional arts so that they are not eroded by the waves of globalization that are currently developing rapidly.